Sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block as well as preparation method and application thereof
By using sodium sulfate and metal oxide to co-dop calcium carbonate-based heat storage blocks in calcium-based heat storage materials, and forming multi-scale pore design through polyurethane foam, the pressure drop problem caused by agglomeration of calcium-based heat storage materials in large reactors is solved, and the material performance of high porosity and high mechanical strength is achieved.
Patent Information
- Application Number
- CN202411870065.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
When existing calcium-based heat storage materials go from the laboratory to large fixed bed reactors, powdered materials are prone to agglomeration, resulting in a large pressure drop during the reaction, making it difficult to apply to industrial production.
Sodium sulfate and metal oxide are used to co-dop calcium carbonate-based heat storage blocks, and polyurethane foam is used as a support and water is used as a foaming agent to introduce millimeter-level pores, and micro- and nano-level pores are formed through calcination to achieve multi-scale pore design.
The high porosity and high mechanical strength of the material are achieved, the gas flow resistance during the reaction process is reduced, the specific surface area and heat storage performance of the material are improved, and the stable performance of the material is ensured during multiple charge and discharge.
Smart Images

Figure CN119661195A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermochemical energy storage, and more specifically to a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block and a preparation method and application thereof. Background Art
[0002] As a key technology for solar energy utilization, concentrated solar power generation has received extensive attention and rapid development in the past few decades. Solar energy resources are susceptible to natural changes and some unpredictable factors, which makes it challenging for concentrated solar power generation to achieve efficient and stable power supply. The addition of thermal energy storage systems makes it possible for concentrated solar power generation to achieve continuous and stable power supply. Calcium cycle is considered to be a promising thermochemical energy storage technology.
[0003] In the existing technology, researchers have stimulated the good heat storage performance of calcium carbonate / calcium oxide-based heat storage materials through modification. However, most of them are based on the powder state in the laboratory stage. However, when the preparation environment changes from the laboratory to a large fixed bed reactor, the powdered CaO-based heat storage material tends to agglomerate severely before and after the cycle, resulting in the obstruction of the inter-particle transmission of the reaction gas and a large pressure drop during the reaction process, so it is difficult to apply it to industrial production. This problem is exacerbated as the size of the reactor increases, resulting in a large deviation in the performance of large-scale applications compared to laboratory-scale tests. Therefore, the development of high-performance energy storage modules has become the key to promoting the further application of thermochemical energy storage technology.
[0004] The porous heat storage module has a high porosity and good material integrity. Because of its high porosity, the heat storage module can avoid a large pressure drop during the reaction process, and the reaction gas can enter the module more smoothly.
[0005] However, traditional single-size porous heat storage modules cannot take into account both high porosity and high mechanical strength. Heat storage modules with low porosity have higher energy storage density and mechanical strength, but will bring about a larger pressure drop, making the reaction unable to proceed fully, and vice versa. Summary of the invention
[0006] In response to the above problems, the present invention provides a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block, a preparation method and an application thereof. The sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block prepared according to the preparation method of the present invention has high porosity and high mechanical strength.
[0007] The first object of the present invention is to provide a method for preparing a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0008] The metal oxide and calcium carbonate are added into the sodium sulfate solution and stirred to obtain a mixed solution.
[0009] The polyurethane foam is immersed in the mixed solution for adsorption to obtain the adsorbed polyurethane foam.
[0010] Under a protective gas atmosphere, the adsorbed polyurethane foam is calcined at 900° C. to 1100° C. to obtain a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block.
[0011] In a preferred embodiment of the present invention, the molar ratio of calcium carbonate to sodium sulfate is 10:0.1-5. For example, the molar ratio of calcium carbonate to sodium sulfate is 10:0.1, 10:0.5, 10:1, 10:1.5, 10:2, 10:2.5, 10:3, 10:3.5, 10:4, 10:4.5, 10:5, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are equally applicable.
[0012] In a preferred embodiment of the present invention, the molar ratio of calcium carbonate to sodium sulfate is 10:1.
[0013] In a preferred embodiment of the present invention, the molar ratio of calcium carbonate to the metal oxide is 10:0.1-10. For example, the molar ratio of calcium carbonate to the metal oxide is 10:0.1, 10:1, 10:2, 10:3, 10:4, 10:5, 10:6, 10:7, 10:8, 10:9, 10:10, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are equally applicable.
[0014] In a preferred embodiment of the present invention, the molar ratio of calcium carbonate to metal oxide is 10:3.
[0015] The metal oxide is zinc oxide, magnesium oxide, copper oxide or aluminum oxide.
[0016] Taking zinc oxide as an example of metal oxides, sodium sulfate will be added to zinc oxide to form coordination compounds Na2Ca(SO4)2 and Na2Zn(SO4)2. During the formation of the coordination compound, expansion will occur, promoting pore formation. It helps to optimize material properties. However, excessive zinc oxide and sodium sulfate will cause blockage of nano-scale pores. When the Na2SO4 content is high, Na2SO4 that has not formed coordination compounds with ZnO and CaO will continue to melt and penetrate into CaO to form a large amount of Na2O to densify the structure and cause material sintering. When the ZnO content exceeds the amount required to form a coordination compound with Na2SO4, the remaining excessive ZnO will cause blockage of capillary channels. This leads to a decrease in the cyclic stability of the material.
[0017] In a preferred embodiment of the present invention, the calcination time is 2h to 3h, for example, the calcination time is 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0018] In a preferred embodiment of the present invention, the pore density of the polyurethane foam is 15PPI to 60PPI. For example, the pore density of the polyurethane foam is 15PPI, 30PPI, 45PPI, 60PPI, etc., but is not limited to the listed values. Other unlisted values within the above numerical range are also applicable.
[0019] The second object of the present invention is to provide a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block prepared by the above preparation method.
[0020] The third object of the present invention is to provide the application of the above-mentioned sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block in a calcium cycle energy storage system. Specifically, the sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block prepared by the present invention can be used in conjunction with concentrated solar power generation to solve the intermittent problem of solar power generation.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) In the preparation of sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage blocks, the present invention uses polyurethane foam as a support and water as a foaming agent to introduce millimeter-level pores according to the foaming principle, and then the polyurethane foam is calcined to form micron-level pores. Calcium carbonate, sodium sulfate and metal oxides form nano-level pores during the calcination process. The millimeter-level pores can reduce the gas flow resistance during the reaction process. The micron-level and nano-level pores can effectively increase the specific surface area of the material, provide more active sites, and improve the heat storage performance of the material. The present invention achieves a fast reaction rate and excellent cycle stability of the material during the heat storage process through a unique multi-size pore design. Multi-scale pores can prevent the material from generating a large pressure drop during the reaction process. Affect the chemical reaction. During the molding process, no mechanical external force is used to avoid damage to the internal structure of the material and retain the characteristics of the material as much as possible. Millimeter-level pores, micron-level pores and nano-level pores are helpful for gas transmission, reducing sintering resistance and improving the reaction efficiency of reactants, respectively. In addition, the multi-scale void structure can improve the bearing capacity of the material and improve the toughness and strength of the material.
[0023] (2) The calcium carbonate, metal oxides and sodium sulfate used in the present invention are all common commercial materials, which reduces the production cost and ensures the extensiveness and sustainability of the material source. The preparation process adopted is concise and easy to operate, does not require complicated equipment or steps, and greatly improves the production efficiency. This multi-scale pore design not only improves the mechanical strength of the material and ensures its durability in practical applications, but also optimizes the cycle stability, so that the material can still maintain stable performance during multiple charge and discharge processes.
[0024] (3) The present invention not only provides a new efficient, simple and economical approach for the development of calcium-based energy storage media, but also achieves a comprehensive improvement in material performance through innovative design and process, making an important contribution to the development of energy storage technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 3 is a morphological diagram of the multi-scale porous heat storage module of Example 2, wherein A is a macroscopic morphological diagram, B is a local enlarged diagram of Figure A, C is a local enlarged microscopic diagram of Figure B, and D is a local enlarged microscopic diagram of Figure C.
[0026] Figure 2 This is the pore distribution diagram of the heat storage module molded with different polyurethane foams. The inset is a local enlarged view.
[0027] Figure 3 The graph shows the cycling stability after 100 cycles with different dopant contents.
[0028] Figure 4 The stability diagram of 100 cycles of doping with different metal oxides.
[0029] Figure 5 The XPS results of doping with different metal oxides.
[0030] Figure 6 This is the cycle stability diagram of the heat storage module after 100 cycles.
[0031] Figure 7 This is the compressive strength diagram of the heat storage module after 100 cycles.
[0032] Figure 8 This is the molding mechanism of polyurethane foam with different PPI.
[0033] Fig. 9 The macroscopic morphology of Example 2 and Comparative Example 2 before and after 100 cycles.
[0034] Fig.10 The void structures of Example 2 and Comparative Example 2 after 100 cycles, and the inset is a partial enlarged view. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] At present, researchers have stimulated the good heat storage performance of calcium carbonate / calcium oxide-based heat storage materials in terms of modification. However, most of them are based on the powder state in the laboratory stage. When leaving the laboratory, it is difficult to apply to industrial production because the powdered heat storage materials are easy to agglomerate in the reactor, resulting in a large pressure drop during the reaction.
[0037] In the past decade, researchers have proposed various powder molding concepts, including particles, honeycombs, and porous foam structures. Conventional particles face large pressure drops in fixed-bed reactors due to agglomeration after circulation, which may lead to reduced gas flow at the reactor outlet, especially in large reactors. In addition, particles are usually small spheres or cylinders with dense surfaces and low porosity. Although this structure may be beneficial to mechanical properties, it hinders the diffusion rate of the reaction gas, thereby affecting the overall performance of the system. Honeycomb thermal storage modules provide an effective solution to the pressure drop problem encountered in packed bed reactors. It can adapt to very high gas flow rates and meet the requirements of rapid heat storage and heat release. There are two subtypes of honeycomb thermochemical energy storage (TCES) modules: material coating and material-based honeycomb. Material coating is to coat TCES materials on the surface of ordinary cordierite or silicon carbide honeycomb ceramic substrates. However, this method is limited by low thermal storage density because the thickness of the coating cannot be arbitrarily thickened. The material-based honeycomb method involves synthesizing honeycomb structures directly from redox TCES materials, solving the problem of low thermal storage density. However, this method relies on strong mechanical external force to cause the original pore structure of the material to be destroyed, resulting in the loss of the inherent properties of the material. A foam-like heat storage module is formed by the polyurethane foam replication method. This method avoids the intervention of mechanical force during the molding process, and the self-supporting structure of the module avoids the introduction of the supporting structure to affect the stored thermal density. The overall performance of this foam module is related to the pore density of the polyurethane foam; the smaller the pore density, the better the mechanical properties and the higher the thermal storage density, and vice versa. However, according to Poisson's leaf law, the flow resistance is inversely proportional to the fourth power of the pore radius. As the pore radius decreases, the gas pressure drop required for the reaction process increases significantly. In short, in order to achieve high thermal storage capacity and excellent mechanical properties at low pressure drop, the thermal storage module should have a self-supporting structure and a hierarchical porous structure. Large pores can reduce the gas flow resistance during the reaction process, while small pores can provide a larger specific surface area, thereby improving the thermal storage performance.
[0038] Based on this, the present invention is based on calcium carbonate, metal oxides and sodium sulfate, and designs the molding of calcium-based powder by adding polyurethane foam. In the molding strategy of layered porous materials proposed in the present invention, multi-size pores are achieved through the synergistic effect of different principles. Millimeter-sized pores are based on the foaming principle, and the pore size is controlled by introducing polyurethane foams with different pore densities. Millimeter-level pores can effectively avoid a large pressure drop during the reaction process. On the other hand, according to the template sacrificial principle, polyurethane foam leaves micron-level pores after high-temperature pyrolysis. According to the coordination principle, carbon dioxide is released by calcining calcium carbonate and sodium sulfate and metal oxides are added to generate a eutectic solid solution, specifically Na2Zn(SO4)2 and Na2Ca(SO4)2, which expands when the solid solution is formed, thereby forming nanoscale pores. Millimeter-level large pores can reduce the gas flow resistance during the reaction process, and micron-level and nanoscale pores can effectively increase the specific surface area of the material, provide more active sites, and improve the heat storage performance of the material.
[0039] The heat storage module with a multi-scale pore structure formed by the above method has a pore span ranging from nanometers to millimeters. For blocks with a single-size pore structure, the larger the pore size, the worse the compressive resistance of the material. For a multi-scale pore structure, while having a high porosity, it has a higher mechanical strength through the following factors. First, the multi-scale pore structure can increase the surface area of the material, thereby providing more contact points to resist external forces and improving the material's bearing capacity. Secondly, this structure can disperse and absorb the stress applied to the material at the microscopic level, reduce stress concentration, and thus improve the toughness and strength of the material. In addition, the multi-scale pore structure can also optimize the elastic modulus and energy absorption capacity of the material through the graded distribution of pores, so that the material can better disperse energy and reduce damage when it is impacted or compressed.
[0040] Examples of different polyurethane foam pore density selections are shown in Table 1.
[0041] Table 1 Implementation plan for different polyurethane foam pore densities and ratio selection
[0042]
[0043]
[0044] Example 1
[0045] This embodiment provides a method for preparing a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0046] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: zinc oxide of 10:1:3. The pore density of the polyurethane foam used in this embodiment is 60 PPI.
[0047] 32g of calcium carbonate and 20g of first deionized water were weighed at a mass ratio of 1.6:1 between calcium carbonate and first deionized water, 7.82g of zinc oxide and 15.6g of second deionized water were weighed at a mass ratio of 1:2 between zinc oxide and second deionized water, 4.54g of sodium sulfate was added after mixing the first deionized water and the second deionized water, and the mixture was magnetically stirred at 800r / min for 30min to obtain a sodium sulfate solution. The weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and stirred at 800r / min for 60min to prepare a mixed solution.
[0048] S2. Pre-molding treatment: immerse 8 cut polyurethane foams with a side length of 1.5 cm into 50 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow so that the polyurethane foams are filled with the mixed solution.
[0049] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and kept warm for 2 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0050] Example 2
[0051] This embodiment provides a method for preparing a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0052] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: zinc oxide of 10:1:3. The pore density of the polyurethane foam is 45 PPI.
[0053] 32 g of calcium carbonate and 20 g of first deionized water were weighed at a mass ratio of calcium carbonate to the first deionized water of 1.6:1, 7.82 g of zinc oxide and 15.6 g of second deionized water were weighed at a mass ratio of zinc oxide to the second deionized water of 1:2, 4.54 g of sodium sulfate was added after mixing the first deionized water and the second deionized water, and the mixture was magnetically stirred at 800 r / min for 30 min to obtain a sodium sulfate solution, the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and the mixture was stirred at 800 r / min for 60 min to prepare a mixed solution.
[0054] S2. Pre-molding treatment: immerse 8 cut polyurethane foams with a side length of 1.5 cm into 50 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow so that the polyurethane foams are filled with the mixed solution.
[0055] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and kept warm for 2 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0056] Example 3
[0057] This embodiment provides a method for preparing a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0058] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: zinc oxide of 10:1:3. The pore density of the polyurethane foam is 60 PPI.
[0059] 32g of calcium carbonate and 20g of first deionized water were weighed at a mass ratio of 1.6:1 between calcium carbonate and first deionized water, 7.82g of zinc oxide and 15.6g of second deionized water were weighed at a mass ratio of 1:2 between zinc oxide and second deionized water, 4.54g of sodium sulfate was added after mixing the first deionized water and the second deionized water, and the mixture was magnetically stirred at 800r / min for 30min to obtain a sodium sulfate solution. The weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and stirred at 800r / min for 60min to prepare a mixed solution.
[0060] S2. Pre-molding treatment: immerse 8 cut polyurethane foams with a side length of 1.5 cm into 50 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow so that the polyurethane foams are filled with the mixed solution.
[0061] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and kept warm for 2 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0062] Example 4
[0063] This embodiment provides a method for preparing a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0064] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: zinc oxide of 10:0.5:3. The pore density of the polyurethane foam is 45 PPI.
[0065] 32 g of calcium carbonate and 20 g of first deionized water were weighed at a mass ratio of calcium carbonate to the first deionized water of 1.6:1, 7.82 g of zinc oxide and 15.6 g of second deionized water were weighed at a mass ratio of zinc oxide to the second deionized water of 1:2, 2.27 g of sodium sulfate was added to the first deionized water and the second deionized water, and the mixture was magnetically stirred at 800 r / min for 30 min to obtain a sodium sulfate solution, the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and the mixture was stirred at 800 r / min for 60 min to prepare a mixed solution.
[0066] S2. Pre-molding treatment: immerse 8 pieces of polyurethane foam with a side length of 1.5 cm into 50 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow to fill the polyurethane foam with the mixed solution.
[0067] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and kept warm for 2 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0068] Example 5
[0069] This embodiment provides a method for preparing a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0070] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: zinc oxide of 10:2:3. The pore density of the polyurethane foam is 45 PPI.
[0071] According to the mass ratio of calcium carbonate to the first deionized water of 1.6:1, 32g of calcium carbonate and 20g of the first deionized water were weighed; according to the mass ratio of zinc oxide to the second deionized water of 1:2, 7.82g of zinc oxide and 15.6g of the second deionized water were weighed; after mixing the first deionized water and the second deionized water, 9.09g of sodium sulfate was added, and the mixture was magnetically stirred at 800r / min for 30min to obtain a sodium sulfate solution; the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and stirred at 800r / min for 60min to prepare a mixed solution.
[0072] S2. Pre-molding treatment: immerse 8 pieces of polyurethane foam with a side length of 1.5 cm into 50 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow to fill the polyurethane foam with the mixed solution.
[0073] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and kept warm for 2 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0074] Example 6
[0075] This embodiment provides a method for preparing a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0076] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: zinc oxide of 10:1:1. The pore density of the polyurethane foam is 45 PPI.
[0077] 32 g of calcium carbonate and 20 g of first deionized water were weighed at a mass ratio of calcium carbonate to the first deionized water of 1.6:1, 2.61 g of zinc oxide and 5.21 g of second deionized water were weighed at a mass ratio of zinc oxide to the second deionized water of 1:2, 4.54 g of sodium sulfate was added to the first deionized water and the second deionized water, and the mixture was magnetically stirred at 800 r / min for 30 min to obtain a sodium sulfate solution, the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and the mixture was stirred at 800 r / min for 60 min to prepare a mixed solution.
[0078] S2. Pre-molding treatment: immerse 6 pieces of polyurethane foam with a side length of 1.5 cm into 50 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow to fill the polyurethane foam with the mixed solution.
[0079] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and kept warm for 2 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0080] Example 7
[0081] This embodiment provides a method for preparing a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0082] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: zinc oxide of 10:1:4. The pore density of the polyurethane foam is 45 PPI.
[0083] 32 g of calcium carbonate and 20 g of first deionized water were weighed at a mass ratio of calcium carbonate to the first deionized water of 1.6:1, 10.42 g of zinc oxide and 20.84 g of second deionized water were weighed at a mass ratio of zinc oxide to the second deionized water of 1:2, 4.54 g of sodium sulfate was added to the first deionized water and the second deionized water, and the mixture was magnetically stirred at 800 r / min for 30 min to obtain a sodium sulfate solution, the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and the mixture was stirred at 800 r / min for 60 min to prepare a mixed solution.
[0084] S2. Pre-molding treatment: immerse 16 pieces of polyurethane foam with a side length of 1.5 cm into 70 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow so that the polyurethane foam is filled with the mixed solution.
[0085] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and kept warm for 2 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0086] Example 8
[0087] This embodiment provides a method for preparing a sodium sulfate and magnesium oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0088] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: magnesium oxide of 10:1. The pore density of the polyurethane foam is 45 PPI.
[0089] 32 g of calcium carbonate and 20 g of first deionized water were weighed at a mass ratio of calcium carbonate to the first deionized water of 1.6:1, 3.87 g of zinc oxide and 7.74 g of second deionized water were weighed at a mass ratio of zinc oxide to the second deionized water of 1:2, 4.54 g of sodium sulfate was added to the first deionized water and the second deionized water, and the mixture was magnetically stirred at 800 r / min for 30 min to obtain a sodium sulfate solution, the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and the mixture was stirred at 800 r / min for 60 min to prepare a mixed solution.
[0090] S2. Pre-molding treatment: immerse 16 pieces of polyurethane foam with a side length of 1.5 cm into 70 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow to fill the polyurethane foam with the mixed solution.
[0091] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and kept warm for 2 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0092] Example 9
[0093] This embodiment provides a method for preparing a sodium sulfate and copper oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0094] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: copper oxide of 10:1:3. The pore density of the polyurethane foam is 45 PPI.
[0095] According to the mass ratio of calcium carbonate to the first deionized water of 1.6:1, 32g of calcium carbonate and 20g of the first deionized water were weighed; according to the mass ratio of zinc oxide to the second deionized water of 1:2, 7.64g of zinc oxide and 15.28g of the second deionized water were weighed; after mixing the first deionized water and the second deionized water, 4.54g of sodium sulfate was added, and the mixture was magnetically stirred at 800r / min for 30min to obtain a sodium sulfate solution; the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and stirred at 800r / min for 60min to prepare a mixed solution.
[0096] S2. Pre-molding treatment: immerse 16 pieces of polyurethane foam with a side length of 1.5 cm into 70 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow to fill the polyurethane foam with the mixed solution.
[0097] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and kept warm for 2 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0098] Example 10
[0099] This embodiment provides a method for preparing a sodium sulfate and aluminum oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0100] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: aluminum oxide of 10:1:3. The pore density of the polyurethane foam is 45 PPI.
[0101] According to the mass ratio of calcium carbonate to the first deionized water of 1.6:1, 32g of calcium carbonate and 20g of the first deionized water were weighed; according to the mass ratio of zinc oxide to the second deionized water of 1:2, 9.79g of zinc oxide and 19.58g of the second deionized water were weighed; after mixing the first deionized water and the second deionized water, 4.54g of sodium sulfate was added, and the mixture was magnetically stirred at 800r / min for 30min to obtain a sodium sulfate solution; the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and stirred at 800r / min for 60min to prepare a mixed solution.
[0102] S2. Pre-molding treatment: immerse 16 pieces of polyurethane foam with a side length of 1.5 cm into 70 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow to fill the polyurethane foam with the mixed solution.
[0103] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min, and kept warm for 2 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0104] Embodiment 11
[0105] This embodiment provides a method for preparing a sodium sulfate and aluminum oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0106] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: aluminum oxide of 10:1:0.1. The pore density of the polyurethane foam is 45 PPI.
[0107] According to the mass ratio of calcium carbonate to the first deionized water of 1.6:1, 32g of calcium carbonate and 20g of the first deionized water were weighed; according to the mass ratio of zinc oxide to the second deionized water of 1:2, 9.79g of zinc oxide and 19.58g of the second deionized water were weighed; after mixing the first deionized water and the second deionized water, 4.54g of sodium sulfate was added, and the mixture was magnetically stirred at 800r / min for 30min to obtain a sodium sulfate solution; the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and stirred at 800r / min for 60min to prepare a mixed solution.
[0108] S2. Pre-molding treatment: immerse 16 pieces of polyurethane foam with a side length of 1.5 cm into 70 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow to fill the polyurethane foam with the mixed solution.
[0109] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 900°C at a heating rate of 10°C / min, and kept warm for 3 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0110] Example 12
[0111] This embodiment provides a method for preparing a sodium sulfate and aluminum oxide co-doped calcium carbonate-based heat storage block, comprising the following steps:
[0112] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: aluminum oxide of 10:1:5. The pore density of the polyurethane foam is 15 PPI.
[0113] According to the mass ratio of calcium carbonate to the first deionized water of 1.6:1, 32g of calcium carbonate and 20g of the first deionized water were weighed; according to the mass ratio of zinc oxide to the second deionized water of 1:2, 9.79g of zinc oxide and 19.58g of the second deionized water were weighed; after mixing the first deionized water and the second deionized water, 4.54g of sodium sulfate was added, and the mixture was magnetically stirred at 800r / min for 30min to obtain a sodium sulfate solution; the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and stirred at 800r / min for 60min to prepare a mixed solution.
[0114] S2. Pre-molding treatment: Soak 12 pieces of polyurethane foam with a side length of 1.5 cm in 70 ml of the mixed solution, and squeeze them repeatedly until no bubbles overflow to fill the polyurethane foam with the mixed solution.
[0115] S3. Calcination molding: In a nitrogen atmosphere, the temperature is increased from room temperature to 1100°C at a heating rate of 10°C / min, and kept warm for 2.5 hours to prepare a sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block.
[0116] Comparative Example 1
[0117] This comparative example provides a method for preparing a calcium-based energy storage medium, comprising the following steps:
[0118] In a nitrogen atmosphere, the calcium carbonate powder was heated from room temperature to 1000°C at a heating rate of 10°C / min and kept at this temperature for 2 hours.
[0119] Comparative Example 2
[0120] This comparative example is a method for preparing a composite heat storage material without adding polyurethane foam, comprising the following steps:
[0121] S1. Weigh each component according to the molar ratio of calcium carbonate: sodium sulfate: zinc oxide of 10:1:3.
[0122] 32 g of calcium carbonate and 20 g of first deionized water were weighed at a mass ratio of calcium carbonate to the first deionized water of 1.6:1, 7.82 g of zinc oxide and 15.6 g of second deionized water were weighed at a mass ratio of zinc oxide to the second deionized water of 1:2, 4.54 g of sodium sulfate was added after mixing the first deionized water and the second deionized water, and the mixture was magnetically stirred at 800 r / min for 30 min to obtain a sodium sulfate solution, the weighed calcium carbonate and zinc oxide were added to the sodium sulfate solution, and the mixture was stirred at 800 r / min for 60 min to prepare a mixed solution.
[0123] S2. Calcination: In a nitrogen atmosphere, the temperature is increased from room temperature to 1000°C at a heating rate of 10°C / min and kept at this temperature for 2h to prepare a composite heat storage material.
[0124] Examples 1-7 and Comparative Examples 1-2 were subjected to a cycle treatment. The cycle condition was to maintain a temperature of 850° C. During this process, CO2 was introduced for 60 minutes and then N2 was introduced for 60 minutes. One cycle was counted as one CO2 and one N2 introduction, and a total of 100 cycles were performed.
[0125] Figure 1 The macroscopic morphology and internal structure diagram of the sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block prepared in Example 2 clearly show that the heat storage module has a complete appearance, crisscrossed large pores inside, and porous structures exist at different scales.
[0126] The pore size of the sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage block was tested by pore testing. Figure 2 As shown, by measuring these millimeter-sized pores, they are mainly concentrated in the range of 0.8mm-1.2mm, which will be conducive to the large amount of reaction gas entering and exiting the thermal storage module to effectively reduce the gas diffusion resistance. The micron-level pore size is mainly concentrated in the range of 2μm-5μm, and the nano-level pore size can be as small as 40nm, which provides sufficient space and specific surface area to improve sintering resistance and reaction efficiency.
[0127] Figure 3The effects of the pores of polyurethane foam on the performance of the heat storage module when preparing sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage blocks for Examples 1-3 and Comparative Examples 1-2. Each material was tested by 100 carbonization / calcination cycles. Compared with Comparative Example 1, the conversion rates of Example 1, Example 2 and Example 3 after 100 cycles increased by 214%, 264% and 230%, respectively. Among them, the conversion rate of Comparative Example 2 after 100 cycles is lower than that of Comparative Example 1. This fully illustrates the importance of molding.
[0128] Figure 4 For comparison of the conversion efficiency of different metal oxides, it can be seen that the conversion efficiency of Example 1 after 100 cycles is increased by 19.2%, 51.2%, and 37.8% respectively compared with Examples 8-10, indicating that the doping effect of zinc oxide is better than that of the other three metal oxides. Figure 5 This is the XPS analysis of O1s of Na2SO4-(CaO+ZnO), Na2SO4-(CaO+MgO), Na2SO4-(CaO+CuO), and Na2SO4-(CaO+Al2O3). The content of chemically adsorbed oxygen (O2) in the thermal storage material doped with zinc oxide is the highest. The higher the content of chemically adsorbed oxygen (O2), the higher the adsorption activity of the composite material.
[0129] Figure 6 The figure is a conversion efficiency diagram of heat storage modules with different material ratios. Compared with comparative example 2, after 100 cycles, the conversion rates of examples 3-7 were increased by 121%, 81.7%, 47.5%, 64.3% and 108%, respectively. This shows that the combined effect of sodium sulfate and zinc oxide can effectively improve the conversion efficiency and cycle stability of calcium oxide.
[0130] Figure 7 The change trend of the compressive strength of different polyurethane foam pores during the cycle process when preparing sodium sulfate and zinc oxide co-doped calcium carbonate-based heat storage blocks for Examples 1-3 and Comparative Example 1. The initial compressive strength of all heat storage modules increased, then decreased, and finally reached a stable state. After 100 cycles, the compressive strengths of Example 1, Example 2, and Example 3 were 0.274 MPa, 0.492 MPa, and 0.554 MPa, respectively. They were all higher than the compressive strength of Comparative Example 1, 0.263 MPa, to varying degrees.
[0131] Figure 8The mechanism of how polyurethane foams with different pore densities affect the foaming process was revealed. When using 30PPI foam, the bubbles have enough space to grow due to the low pore density. Since the gas pressure inside the bubble is inversely proportional to its radius, smaller bubbles will exhibit higher internal pressures. When bubbles of different sizes approach each other, the gas diffuses from the smaller bubbles to the larger bubbles, causing them to merge. As the volume of the bubbles continues to increase, the surface tension and viscosity of the solution are not sufficient to suppress the movement of the bubbles, and the gas will be lost from the material to the atmosphere. The space previously occupied by the bubbles is filled with the solution. As the water vapor is continuously discharged, the structure gradually stabilizes. As Figure 8 As shown in the figure, large particles are accumulated inside the thermal storage module. As the cycle reaction proceeds, the surface of the large particles sinters, blocking the entry of carbon dioxide and causing a decrease in conversion efficiency. This large particle accumulation structure leads to weak connections between particles and weak compressive strength.
[0132] As the pore density of polyurethane foam increases to 45PPI, the bubbles will split into polyurethane foam structures when they grow to a certain pore size. Some bubbles merge with other bubbles and are discharged, while the remaining bubbles cannot move due to the surface tension and viscosity of the solution. As the water evaporates, the structure of the thermal storage module tends to stabilize. Some interconnected bubbles are fixed. Figure 8 As shown, an interconnected porous structure network is formed.
[0133] When the pore density of polyurethane foam increases to 60PPI, the expansion of bubbles will be overly restricted by the polyurethane structure due to the small pores in the polyurethane foam. Compared with the pore density of polyurethane foam of 45PPI, as the structure of the thermal storage module gradually stabilizes, more small bubbles are isolated by the solution wall membrane to form an independent pore structure, such as Figure 8 As shown. This structure hinders the diffusion of gas. Therefore, the conversion rate of the sodium sulfate and zinc oxide co-doped calcium carbonate-based thermal storage block prepared with a pore density of 60 PPI of polyurethane foam after 100 cycles is slightly lower than that of the sodium sulfate and zinc oxide co-doped calcium carbonate-based thermal storage block prepared with a pore density of 45 PPI of polyurethane foam. And this independent pore structure helps to improve the compressive strength.
[0134] When the traditional calcium-based heat storage material molding method is used on a large scale in a fixed bed, the granular calcium-based material will agglomerate, which will lead to a large pressure drop during the reaction. Honeycomb or foam energy storage modules only have pores of a single scale, and it is difficult to balance energy storage density and mechanical properties. Therefore, the multi-scale pore distribution of the heat storage module can effectively balance the heat storage performance and mechanical strength of the material. Specifically reflected in the cycle conversion rate, the cycle conversion rate is the CO2 that can be absorbed per unit of calcium oxide. The higher the cycle conversion rate, the higher the CO2 adsorption performance of the calcium oxide in the material.
[0135] Fig. 9 The macroscopic morphology of Example 2 and Comparative Example 2 before and after 100 cycles is shown in Figure 2. It can be clearly seen that Comparative Example 2 has obvious agglomeration, while Example 2 maintains structural integrity before and after the cycle. This further proves the structural stability of the molding material. Fig.10 The void structures of Example 2 and Comparative Example 2 were characterized after 100 cycles. The results show that Example 2 still has stepped pores, while the number of void structures in Comparative Example 2 is very small due to the combined effects of agglomeration and sintering.
[0136] It should be noted that in the preparation process of the present invention, when adding polyurethane foam to the mixed solution in step S2, the number of polyurethane foams is not limited, and different numbers of polyurethane foams, such as 6 to 16, can be added according to experimental requirements. It is understandable that when the number of polyurethane foams added is large, the volume of the mixed solution needs to be increased so that each polyurethane foam is filled with the mixed solution. In addition, the polyurethane foam used can be cut into a desired shape as needed. In the preparation process of the present invention, a 1.5 cm cube is cut for use.
[0137] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0138] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block, characterized in that: The following steps are involved: The metal oxide and calcium carbonate are added into the sodium sulfate solution and stirred to obtain a mixed solution; The polyurethane foam is immersed in the mixed solution for adsorption to obtain the adsorbed polyurethane foam; Under a protective gas atmosphere, the adsorbed polyurethane foam is calcined at 900° C. to 1100° C. to obtain a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block.
2. The method for preparing a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block according to claim 1, characterized in that: The molar ratio of calcium carbonate to sodium sulfate is 10:0.1-5.
3. The method for preparing a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block according to claim 2, characterized in that: The molar ratio of calcium carbonate to sodium sulfate is 10:
1.
4. The method for preparing a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block according to claim 1, characterized in that: The molar ratio of calcium carbonate to metal oxide is 10:0.1-10.
5. The method for preparing a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block according to claim 4, characterized in that: The molar ratio of calcium carbonate to metal oxide is 10:
3.
6. The method for preparing a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block according to claim 1, characterized in that: The metal oxide is zinc oxide, magnesium oxide, copper oxide or aluminum oxide.
7. The method for preparing a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block according to claim 1, characterized in that: The calcination time is 2h to 3h.
8. The method for preparing a sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block according to claim 1, characterized in that: The pore density of polyurethane foam is 15PPI~60PPI.
9. A sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the sodium sulfate and metal oxide co-doped calcium carbonate-based heat storage block according to claim 9 in a calcium cycle energy storage system.
